Chapter Privacy online tra bambini e adolescenti: concezione, preoccupazione e tutela - Vespoli, Giovanni (Studies on Adult Learning and Education, 2022)
The general aim of this study is to investigate how kids and adolescents conceptualize online privacy and the concern about their online privacy through a developmental perspective, while also trying to understand its impact on a safe online surfing environment. Three studies were conducted: 1) a systematic review, which was aimed to clarify the relative strengths and weaknesses of the literature about the construct of online privacy and online privacy concerns among kids and adolescents; 2) a qualitative study, aimed to understand how adolescents define - and consequently understand - the concept of online privacy; 3) a quantitative study, which aimed at addressing whether online surfing is associated with online privacy concerns and with GDPR (General Data Protection Regulation) differently across different ages during adolescence. Finally, the results of the three studies were analysed and discussed in light of the theory background. An analysis of the literature showed how children may have difficulties to fully understand risks in unusual contexts, and that they can have difficulties in responding to situations when they struggled to recognise or understand fully the risks involved. The results of the three studies are discussed, underlining how adolescents understand their online privacy, if they are concerned about their data online, how we should help them manage better their privacy online, and how we should design services, applications and devices to help kids understand better the implication of the Internet on their 'onlife' (Floridi, 2015).